The Importance of Seeking Truth: Lessons from al-Ghazali - Prasetia, Senata Adi (Tebuireng: Journal of Islamic Studies and Society, 2023)
This article critically examines how al-Ghazali carries out the process of seeking truth and its contextualization in contemporary Indonesian Islam. al-Ghazali entered a deep crisis because of his doubts about the senses and reason and described this state as "psychological instability". This state is considered to be the culmination of a process of doubt (i.e. existential doubt), which is compared to a disease that has a profound effect on one's being. The article argues that al-Ghazali's quest for truth began with doubt and skepticism of questions he could not answer. Moreover, al-Ghazali's doubt is an intellectual method and approach of critical thinking that aims at purifying knowledge from faults and impurities and at revealing the truth of things. I believe that doubt as Al-GhazÄlÄ« sees it is a reviewing of the sources of knowledge and criticizing them again. It is also a critical rethinking of data that are considered implicitly correct in the social and epistemological consciousness, or taken for granted. The views expressed in this article are meant to reflect the religious beliefs of the author. Rather, this article is intended to illustrate the life lessons that can be learned from al-Ghazali's life through the lens of the Hero's Journey in seeking truth.